Fostering fraternity in humanity: the Church’s efforts to bring compassion within the framework of religious moderation - Dorlan Naibaho; Sandy Ariawan; Simion Diparuma Harianja; Jungjungan Simorangkir; Maringan Sinambela (KURIOS (Jurnal Teologi dan Pendidikan Agama Kristen), 2022)
The nature of religion which refers to etymological studies clearly aims so that human life is not chaotic, so it is not surprising that all religions teach goodness. Only the lofty ideals of each religion cannot be adequately implemented among the grassroots so that it is presented precisely as violence and intolerance between adherents of one religion with another religion. Abuse in the name of religion occurs and becomes the beginning of the legitimacy of acts of violence in the cloak of religion. Reconciliation efforts are the church’s responsibility because the church has significant power in society and the church becomes a representation of God that brings the mandate and spirit of reconciliation to the world. The church is also the holder of the baton of Jesus' ministry on earth. In the historical reality of human life, Jesus is the only one who can do good and right throughout His life. The angel called him "Holy, Son of God" (Luk. 1:35), which is confirmed in Hebrews 4:15 "...but was in all points tempted like as we are, yet without sin.” While other humans are only able to implement the bad, or the combination of good and evil, because of human sinfulness. Only by faith in Jesus is a man justified and put before God. Through the power of the Holy Spirit that exists within believers, a wrong thread can be decided and enabled to live life as a new creation, that is, as children of God. The study aims to look at the extent of the church's role in preparing congregation spirituality within the framework of religious moderation, and at the same time reconcile congregations who experience intimidation. The method used in this study was a mix-method, where for some parts that need enrichment, structured interviews were carried out, but in the general part, generalizations were carried out as a result of quantitative data. The respondents in the study numbered 30 people from churches in potentially intolerant areas. In the results of the data with SPSS, it is known that the church’s role in cultivating a system of values, spiritual principles, and a solid theological foundation for the congregation influenced religious moderation by 89.3%, while other factors influence the other 10.7%. Further, it is shown that only 30% of respondents feel equipped with the content of religious moderation in a structured and "prepared" spiritually in case of clashes/friction with other religious people.